2021
DOI: 10.1111/jebm.12443
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges of network meta‐analysis

Abstract: In the past years, network meta-analysis (NMA) has been widely used among clinicians, guideline makers, and health technology assessment agencies and has played an important role in clinical decision-making and guideline development. To inform further development of NMAs, we conducted a bibliometric analysis to assess the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 130 publications
(280 reference statements)
0
15
0
Order By: Relevance
“…Such conflicting results make it challenging for clinicians to accurately provide prognostic data for patients in this area. Comparison of several autograft choices simultaneously, possible through a network analysis [39], would allow for inference regarding the relative effect of these treatments as it pertains to donor site morbidity. Furthermore, this approach may prove valuable by allowing comparisons of interventions that may not have been directly compared in head‐to‐head trials and providing clarity as it pertains to the conflicting results observed with prior direct comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Such conflicting results make it challenging for clinicians to accurately provide prognostic data for patients in this area. Comparison of several autograft choices simultaneously, possible through a network analysis [39], would allow for inference regarding the relative effect of these treatments as it pertains to donor site morbidity. Furthermore, this approach may prove valuable by allowing comparisons of interventions that may not have been directly compared in head‐to‐head trials and providing clarity as it pertains to the conflicting results observed with prior direct comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…The recent growth of network meta-analysis (NMA) has revolutionized outcomes research and our abilities to compare treatments to improve patient outcomes. 1 Despite this innovation, most evidence synthesis of health service interventions (HSI) have focused on exploring the effect of interventions rather than how to deliver such interventions. 2 To fill this gap, a framework classifying delivery by Theme (T), Intensity (I), and Provider/Platform (P) (TIP framework) was developed.…”
Section: The Potential Benefits Of the Tip Framework To Characterize ...mentioning
confidence: 99%
“…Furthermore, it avoids the inflation of type I errors (multiplicity) introduced by performing a series of head-to-head comparisons. [23]…”
Section: Comparative Studiesmentioning
confidence: 99%